2018
DOI: 10.1159/000495829
|View full text |Cite
|
Sign up to set email alerts
|

Sestrin 2 Attenuates Rat Hepatic Stellate Cell (HSC) Activation and Liver Fibrosis via an mTOR/AMPK-Dependent Mechanism

Abstract: Background/Aims: Sestrin 2 is associated with the pathophysiology of several diseases. The aim of this study was to investigate the effects and potential mechanisms of Sestrin 2 in rat hepatic stellate cells (HSCs) during liver fibrogenesis. Methods: In this study, Sestrin 2 protein expression was detected in rat HSC-T6 cells challenged with transforming growth factor-β (TGF-β) and in mice treated with carbon tetrachloride (CCl4), a well-known model of hepatic fibrosis. Next, HSC-T6 cells and fibrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Sestrin2, a critical antioxidant protein, plays a protective role in antioxidant defense and functions to reduce intracellular reactive oxygen species (ROS) [32][33][34][35]. Emerging evidence have shown that ses-trin2 plays a vital role in the formation and development of fibrosis in many organs, including the heart, liver and kidney [8,[36][37][38]. To further explore whether sestrin2 is related to airway remodeling in COPD, immunohistochemical staining in the airway was done and showed that there was a significantly higher expression of ses-trin2 in the airway in the COPD group compared with the control group, especially in the bronchial epithelial cells, which are replete with MMP9.…”
Section: Discussionmentioning
confidence: 99%
“…Sestrin2, a critical antioxidant protein, plays a protective role in antioxidant defense and functions to reduce intracellular reactive oxygen species (ROS) [32][33][34][35]. Emerging evidence have shown that ses-trin2 plays a vital role in the formation and development of fibrosis in many organs, including the heart, liver and kidney [8,[36][37][38]. To further explore whether sestrin2 is related to airway remodeling in COPD, immunohistochemical staining in the airway was done and showed that there was a significantly higher expression of ses-trin2 in the airway in the COPD group compared with the control group, especially in the bronchial epithelial cells, which are replete with MMP9.…”
Section: Discussionmentioning
confidence: 99%
“…20 SIRT7 locates in nucleus and participated in the ribosomal RNA transcription, cell metabolism, cell stress and DNA damage repair. 21 AMPK has been proved involved in the pathophysiology of liver fibrosis, 22 and up-regulation of AMPK phosphorylation facilitated to the attenuation of liver fibrosis. 23 Interestingly, SIRT3 has been reported as a downstream effector of AMPK in several disease models, and activation of AMPK-SIRT3 signalling contributes to the improvement of mitochondrial function, thus alleviating the progress of diseases.…”
Section: The Active Ingredients Extracted From Traditional Chinesementioning
confidence: 99%
“…Emerging evidence have shown that sestrin2 plays a vital role in the formation and development of brosis in many organs, including heart, liver and renal (8,(29)(30)(31). Consistent with previous reports (19,24,32), the serum concentration of MMP9 was signi cantly increased in the COPD group in our study.…”
Section: Discussionmentioning
confidence: 99%